Upside down: Reframing European Defence Studies. (September 2019) - Meijer, Hugo; Wyss, Marco
Since the end of the Cold War, the study of European defence has been dominated by a 'Common Security and Defence Policy (CSDP)-centric' approach, while largely neglecting the comparative analysis of national defence policies. This article makes a conceptual and empirical case for turning the dominant research prism of European defence studies upside down by returning the analytical precedence to the national level. This approach privileges the comparative analysis of national defence policies and armed forces, before focusing on the trans-/supra-national level. The case for this analytical turn is made in three steps. Firstly, it addresses the different historical stages in European defence integration and the transformation of national armed forces and thereby brings to light the recent renationalization of defence in Europe. Secondly, it questions the predominance of the CSDP in the scholarly literature on European defence. Finally, it seeks to demonstrate the fruitfulness of such a démarche by empirically substantiating common patterns and intra-European divergences in the evolution of national defence policies and armed forces since the end of the Cold War. After having shown the need and added benefit of turning the analytical lense of European defence studies on its head, the conclusion suggests future avenues of research on national defence policies and armed forces in Europe.